APPLICATION OF VOCABULARY TO CHILDREN WITH EDUCATIONAL GAMES - Rahmawati Rahmawati; Somawati Somawati (Universitas Indraprasta PGRI, 2020)
Abstract: Professionalism of a teacher is not only required to teach well, but can guide thedevelopment of children, especially in the application of vocabulary in early childhood, becausenot all children at an early age can apply vocabulary properly and correctly. This study aims toapply vocabulary to children using educational games (APE). This type of research usedquantitative descriptive, as a sample of 18 students of TK AL-AFLAH, data collection using asurvey. The formulation of the problem in this research is How difficult are the teachers in guidingchildren towards learning, especially in applying vocabulary to children. The results showed thatthe application of vocabulary in children with educational play tools increased, so that the learningprocess could be optimal with educational play tools that were able to stimulate all early childhooddevelopment.Key Words: Vocabulary, early childhood, educational play tools (APE)